Capsaicin in the control of Spodoptera frugiperda in corn (Zea mays L.) var. Blanco Urubamba - Herrera , Hecar; Valverde-Rodríguez, Agustina; Castillo , Manuel; Barrionuevo, Laura; Alvarez-Benaute, Luisa; Campos-Albornoz, Miltao (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) causes severe losses in corn (Zea mays L.) crops, which leads to the evaluation of sustainable management alternatives. The objective of this research was to determine the efficacy of capsaicin in controlling S. frugiperda in the corn Blanco Urubamba var. A randomized complete block design with six treatments and three replicates was used: four concentrations of water-soluble capsaicin (6.70; 10.05; 13.40 and 16.75 mL.L-¹), rocoto pepper extract (Capsicum pubescens Ruiz & Pav. (Solanaceae), 50 g.L-¹), and an absolute control. Applications were made at 80, 90, 100, 110, and 120 days after sowing (das). The 16.75 mL.L-¹ dose was the most effective, reducing larval density from 3.12 to 0.13 larvae per plant, and the infestation percentage from 61.12 to 2.78 %, with a control efficacy of 96.69%. Intermediate concentrations (13.40 and 10.05 mL.L-1) also showed significant effects, with final efficacies of 93.83 and 85.19 %, respectively. T1 had moderate efficacy (78.30%), while T5 recorded the lowest control values ​​(72.86 %), with increasing infestations being observed in the control. In terms of yield, T4 (16.75 mL.L-¹) produced ears of 16.77 cm in length and 385.13 g in average weight, reaching a yield of 17.12 t.ha-¹ compared to 9.54 t.ha-¹ for the control. In conclusion, water-soluble capsaicin, especially at 16.75 mL.L-¹, proved to be an effective and sustainable alternative for the management of S. frugiperda in corn.